Kajian Empiris Faktor-Faktor yang Mempengaruhi Adopsi Teknologi Pengolahan Limbah Pada Peternakan Sapi Potong Di Kecamatan Bantarujeg - Maman Sulaeman; Ulfa Indah Laela Rahmah; Oki Imanudin (Tropical Livestock Science Journal, 2026)
This study aims to analyze the factors influencing the adoption of waste management technology on beef cattle farms in Bantarujeg District, Majalengka Regency. The technologies in question include the utilization of animal waste through composting treatment. This study employed a quantitative method with a survey approach involving 173 livestock farmers. The impact of independent variables on the technology adoption rate (the dependent variable) was analyzed using multiple linear regression. The results showed that of the seven variables tested (age, education, livestock farmer attitudes, business scale, extension intensity, livestock farming experience, and access to information), only access to information had a significant effect on the adoption rate (p < 0.001). The adoption rate of waste management technology is generally low, compared to the majority of livestock farmers who have not yet implemented sustainable waste management. The main obstacles faced by livestock farmers include limited access to information, lack of technical assistance, and low awareness of the environmental and economic benefits of waste management technology. This study recommends increasing the intensity of extension services and access to relevant information, as well as government policy support to encourage livestock farmers to adopt waste management technology more widely.